(untitled) (Research, Society and Development, 2021)
In the last decades, Physical Education since resolution nº 218/97, which recognizes the physical education professional (PEP) as a health professional with a higher education level, has been included in the Primary Health Care (PHC) programs. This study aims to analyze the spatial distribution of PEP bachelors working in PHC in the State of Pará, as well as the offer of vacancy by Higher Education Institutions (HEIs). The study was developed through a survey in the online databases CNESNet, eMEC, websites of the IES and the Regional Council of Physical Education of the State of Pará and had as its coverage area the 6 mesoregions of the State of Pará. As a result, it was verified that the PEP has a performance of only 14.4% in PHC, being present in only 51.25% of the municipalities in Pará and mainly in the NASF-AB program with 45%. Regarding HEIs, it was observed that the on-campus Bachelor course provides 24.7% more vacancies annually, as well as its offer is predominantly in private institutions. There has been a great advance in e-learning, in which case the prevalence of the graduation modality. At the end of the study, we can conclude that PE despite the great advances in the field of public health in recent years, there is still a need for greater awareness of both the professional already inserted in the labor market, the undergraduate and also by the HEI, with the insertion of more disciplines focused on collective health.